Resilience in Nurses Working Shift Work in Australia - Tahghighi, Mozhdeh (Curtin University, 2018)
The aim of this study was to investigate the impact of shift work on resilience and associated mental health and professional quality of life of nurses. Overall, this study found nurse shift workers had significantly lower levels of compassion satisfaction compared to non-shift workers, and they are coping with unique stressors that are in addition to the general stress all nurses are facing.